2020
DOI: 10.4103/jfmpc.jfmpc_186_20
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus-myositis overlap syndrome with lupus nephritis

Abstract: Systemic lupus erythematosus-myositis overlap syndrome is rare with prognostic implications. Reports suggest that systemic lupus erythematosus-myositis overlap syndrome with lupus nephritis has a variable clinical outcome. We report a case of systemic lupus erythematosus-myositis overlap syndrome with lupus nephritis in a 28-year-old female, who presented with facial puffiness, proximal muscle weakness, and proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Renal involvement in SLE occurs in 20-50 % of cases during their disease course [10]. In the present study, 43.7% of cases had renal involvement as documented by renal biopsy.…”
Section: Discussionsupporting
confidence: 48%
“…Renal involvement in SLE occurs in 20-50 % of cases during their disease course [10]. In the present study, 43.7% of cases had renal involvement as documented by renal biopsy.…”
Section: Discussionsupporting
confidence: 48%
“…Regarding the management of this case, glucocorticoids are usually used in the flare-up of SLE and myositis to achieve remission while tapering the dose and replacing it with hydroxychloroquine or an immunosuppressant. Nevertheless, patients with lupus nephritis are treated with an anti-inflammatory immediately, followed by a potent immunosuppressive agent usually for three to six months, and a maintenance phase that lasts for three years [ 2 , 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These myopathies are further subcategorized into four main subtypes based on both the clinical phenotype and histopathology, namely, dermatomyositis, polymyositis, inclusion body myositis, and necrotizing myopathies [ 3 ]. To date, many myositis-associated and specific autoantibodies have been detected and their clinical significance on manifestation and prognosis have been elucidated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that myositis in SLE responds well to corticosteroids. This patient is closely monitored for SLE-myositis overlap syndrome, as this could lead to poor prognosis, especially when there is evidence of pulmonary involvement [ 41 ].…”
Section: Discussionmentioning
confidence: 99%